Conflicting representations on Armenian genocide: exploring the relational future through self-inquiring technique - Mamali, Cătălin; Kivu, Mircea; Kutnik, Jan (Filozofia Publiczna i Edukacja Demokratyczna, 2019)
Major lethal conflicts (war crimes, genocides) between large social actors include many times opposing social representations, narratives and practical approaches to the events worked out by those placed on the aggressor or aggressed, perpetrators or victims’ side. War crimes and genocides seem to be historically associated, mainly in the case of dictatorial regimes, with system-atic repression not only of the information about such events but also of the interrogative potential of common people about the events. The study proposes that such conflicting representations cannot be approached only by questions pre-established by the researchers to which the participants are supposed to answer. Methodologically and theoretically it is justified to explore the assumptions and the questions that can be triggered by the presentation of conflicts to the participants who are supposed to look to the same conflict from both sides. Besides the use of national representative samples and of convenience samples before and after the 100 years commemoration of the 1915 Armenian genocide the study presents the findings based on self-inquiry technique applied at three levels of social complexity: (a) societal level, with questions directed to the general universe of discourse implied by the 1915 events; (b) at interpersonal level with questions directed to actors with leading roles on both sides; (c) at the individual level stimulating questions about 1915 genocide that are explicitly self-directed. We suggest, based on the findings, that the expression of the questioning potential on tragic events is useful for the relational future of the sides involved in the conflicts.